UPAYA MENINGKATAN KOPETENSI GURU KELAS RENDAH DALAM MENYUSUN ADMINISTRASI PEMBELAJARAN MELALUI SUPERVISI AKADEMIK PADA MASA PANDEMI COVID-19 DI SDN KEDUNGDORO V/310 SURABAYA - SUMARTINI SUMARTINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This research is a school action research (PTS) which raises about how teachers can use the existing learning administration in the learning process in the classroom with the intention of increasing the quality of learning carried out in the classroom and the evaluation is carried out through the supervision of the principal in the classroom during learning. This school action research activity was carried out at SDN Kedungdoro V/310 for 3 months, starting from July to September 2021 by going through cycle stages. The purpose of this school action research (PTS) is to determine the extent to which the supervision carried out by the principal followed by the provision of guidance/treatment to the target teachers can increase the competence of the low-grade teachers in preparing learning administration. In this school action research (PTS), it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase the competence of low grade teachers by achieving ideal standards. In the first cycle, the increase in the competence of low-grade teachers in preparing learning administration reached about 33.33%, in the second cycle it could increase to 100%. The average score obtained after class supervision in the first cycle was 71.33 and increased in the second cycle to 83.33, meaning that there was an increase of 12 and the level of completeness as a group/classical in the first cycle reached 33.33% and in the first cycle it was 33.33%. II increased to 100%. The results of this school action research indicate that the coaching of the principal can improve the competence of low-grade teachers in preparing learning administration. ABSTRAKPenelitian yang dilakukan ini merupakan penelitian tindakan sekolah (PTS) yang mengangkat tentang bagaimana guru dapat menggunakan administrasi pembelajaran yang ada dalam proses pembelajaran di kelas dengan maksud dapat meningkat kualitas pembelajaran yang dilakukan di kelas dan evaluasinya dilakukan melalui kegiatan supervise kepala sekolah di kelas saat pembelajaran. Kegiatan penelitian tindakan sekolah ini dilakukan di SDN Kedungdoro V/310 selama 3 bulan yaitu mulai bulan Juli sampai dengan September 2021 dengan melalui tahapan-tahapan siklus. Tujuan dari penelitian tindakan sekolah (PTS) ini adalah untuk mengetahui sejauh mana supervisi yang dilakukan oleh kepala sekolah yang diikuti dengan pemberian pembinaan/perlakuan terhadap guru-guru sasaran dapat meningkatkan Kopetensi guru kelas rendah tersebut dalam menyusun administrasi pembelajaran. Dalam penelitian tindakan sekolah (PTS) ini dilakukan dalam 2 siklus, dari hasil tindakan yang dilakukan terbukti dapat meningkatkan Kopetensi guru kelas rendah dengan mencapai standar ideal. Pada siklus I peningkatan Kopetensi guru kelas rendah dalam menyusun administrasi pembelajaran mencapai sekitar 33,33 % ,pada siklus II dapat meningkat menjadi 100 %. Skor rata-rata yang diperoleh setelah dilakukan supervisi kelas pada siklus I sebesar 71,33 dan meningkat pada siklus II menjadi 83,33, berarti ada peningkatan sebesar 12 dan tingkat ketuntasan secara kelompok/klasikal pada siklus I mencapai 33,33% dan pada siklus II meningkat menjadi 100 %. Hasil penelitian tindakan sekolah ini menunjukkan bahwa pembinaan kepala sekolah dapat meningkatkan Kopetensi guru kelas rendah dalam menyusun administrasi pembelajaran.